Negotiating Identity through Code-Switching: English and Buginese Language in Academic and Social Discourse - Muhammad Zuhri Dj; Farida; Andi Muhammad Yauri; Ahmad Rossydi; Andi Adisaturrahimi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
This study examines at the sociolinguistic phenomena of code-switching among English-Buginese bilingual university students, with a focus on how it helps them negotiate their identities in academic and social settings. Using a qualitative case study approach, data were collected from simulated but contextually authentic interactions such as classroom discussions, peer conversations, and semi-structured interviews. Based on Gumperz's (1982) interactional sociolinguistics and Myers-Scotton's (1993) markedness model, the analysis identified three types of code-switching: inter-sentential, intra-sentential, and tag-switching. The findings show that in academic settings, English is frequently employed to communicate formality, academic authority, and alignment with global academic discourse, whereas Buginese is utilized to maintain solidarity, cultural identity, and shared heritage. In social situations, code-switching promotes humor, emotional expression, and pragmatic efficiency. Switching can be triggered by topic switches, lexical gaps, emphasis, or audience adjustment. The findings show that code-switching is not just a linguistic alternation, but also a conscious communicative resource for identity formation. These findings help to better understand bilingual language behaviors in multilingual societies and have implications for bilingual education and language policy in Indonesia.